Study of Sludge Accumulation Rate and Sediment Distribution in Kalidami Boezem, Surabaya - Aisyah Umi; Nurhayati Ervin; Slamet Agus; Masduqi Ali; Setiadi Soedjono Eddy; Djoko Marsono Bowo; Arliyani Isni (BIO Web of Conferences)
Kalidami Boezem is one of Surabaya City’s boezems that is used as a flood control. This boezem can experience silting due to solids that settle from domestic wastewater entering the boezem. This causes decrease in Kalidami Boezem’s volume. The implementation of sludge dredging as boezem maintenance has not been based on accumulation of deposited sludge and sediment distribution. The research included analysis of degradation rate, total solid, and total suspended solid. Sludge sampling was conducted once at inlet, middle, and outlet boezem. Sludge degradation rate was analyzed for 25 days with gravimetric analysis and reaction kinetics approach. Water sampling for sludge accumulation rate analysis was conducted for 7 consecutive days. Sludge accumulation rate was calculated based on the difference in total solid at inlet and outlet. Water sampling for sediment distribution mapping was conducted 3 times a week. Sampling points for sediment distribution mapping amounted to 15 points based on transects 60 m x 30 m. The results of TSS analysis from each transect will be mapped using Surfer 23. Degradation rate of sludge in Kalidami Boezem is 0.0005/day. Sludge occupies 1.65% of the effective storage boezem’s volume with accumulation rate of 1780.484 m³/year. Sediment distribution decreased from inlet to outlet due to settling velocity, flow based on Reynold’s number, settling velocity, flow velocity at each transects point, dredging, and pumping activities. The settling velocity is greater than the water flow velocity so that more solids are sedimented at the inlet of the boezem.